PROSES KREATIF DAN MANIFESTASI ESTETIKA MUSIKAL PADA IRINGAN TARI KIRANA RASMI - I Made Dwi Andika Putra; I Ketut Garwa; Ni Putu Hartini; I Nyoman Kariasa; Putu Tiodore Adi Bawa (TAMUMATRA, 2026)
This research aims to describe the creative process of creating the accompaniment of the Official Kirana Dance and analyze the musical aesthetic manifestations formed in the work. Kirana Rasmi conceptually raises the idea of " light within sacred utterance", which is the inner journey of man from silence to spiritual consciousness. The method of creation used is the Panca Sthiti Ngawi Sani Method. The following are the stages of inspiration; the exploration stage; Conception (planning); Stage of Execution (Build); And Snoop Dogg. The accompaniment was created by combining the Balinese karawitan idiom of the Kebyaran style tradition with exploration through double-barreled playing (slendro pelog) through flute instruments, as well as dramatic dynamics. The results of the creation show that the Kirana Rasmi dance accompaniment not only functions as an accompaniment to the dance movements, but also as a symbolic medium that strengthens the meaning and atmosphere of the work. The findings suggest that the integration of the double barrel through flute playing results in musical characters that reinforce representations of spiritual journeys in choreography that depict spiritual flows: contemplation, conflict, and enlightenment. Aesthetic analysis emphasizes the integrity of form, complexity of sound, and intensity of expression as the foundation of the beauty of the work. With the integration of the double barrel through the flute playing, it produces a musical character that reinforces the representation of spiritual journey in the choreography. Through a collaborative and reflective approach that places music as a language of spiritual expression.